Digitization of Historical and Cultural Heritage: Technology and Management - Lobuzin, I. V. (Інститут проблем реєстрації інформації НАН України, 2012)
The range of issues related to the formation of libraries of digital resources has been considered. The main technological steps to be needed for creation of a digital library and digital storage have been determined. A software and technology solutions to address the main challenges of forming the historical and cultural digital resources of The Vernadsky National Library of Ukraine are proposed. Fig.: 1. Refs: 19 titles.